Evaluation and optimisation of propofol pharmacokinetic parameters in cats for target‐controlled infusion. (14th May 2016) - Cattai, A.; Pilla, T.; Cagnardi, P.; Zonca, A.; Franci, P.
Abstract : The aim of this study was to develop and evaluate a pharmacokinetic model‐driven infusion of propofol in premedicated cats. In a first step, propofol (10 mg/kg) was administered intravenously over 60 seconds to induce anaesthesia for the elective neutering of seven healthy cats, premedicated intramuscularly with 0.3 mg/kg methadone, 0.01 mg/kg medetomidine and 2 mg/kg ketamine. Venous blood samples were collected over 240 minutes, and propofol concentrations were measured via a validated high‐performance liquid chromatography assay. Selected pharmacokinetic parameters, determined by a three‐compartment open linear model, were entered into a computer‐controlled infusion pump (target‐controlled infusion‐1 (TCI‐1)). In a second step, TCI‐1 was used to induce and maintain general anaesthesia in nine cats undergoing neutering. Predicted and measured plasma concentrations of propofol were compared at specific time points. In a third step, the pharmacokinetic parameters were modified according to the results from the use of TCI‐1 and were evaluated again in six cats. For this TCI‐2 group, the median values of median performance error and median absolute performance error were −1.85 per cent and 29.67 per cent, respectively, indicating that it performed adequately. Neither hypotension nor respiratory depression was observed during TCI‐1 and TCI‐2. Mean anaesthesia time and time to extubation in the TCI‐2 group were 73.90 (±20.29) and 8.04 (±5.46) minutes, respectively.